Uvajanje blagovne znamke majoneze Hellmann's na slovenskem trgu - Študija primera - Štular, Milena (Akademija MM, 1997)
The reason why Kolinska had to switch the brand of mayonnaise from Thomy to Hellmannęs is in the ownership of Thomy and Knorr brands. The owner of Thomy is Nestle and the owner of Knorr is CPC. Until the end of 1995 Kolinska produced different products for Nestle and CPC. In 1995 Kolinska had to decideonly for one company. They decided for CPC.
Keywords: blagovne znamke; brand names; Majoneza Hellmann's; marketing; Slovenia; Slovenija; Študije primerov; trženje